Research and development of the ESG agenda on the Russian market in the conditions of the world geopolitical situation - V. V. Degtyareva; D. A. Murzintseva (Вестник университета)
The object of this article is a study of the ESG agenda for Russian business in the changed geopolitical conditions. The statistical data used in the study were collected by the authors from open sources posted on the Internet and printed publications. The main purpose of the study was to identify ESG strategies of companies, their development, and to define key drivers of the development of the ESG agenda in Russia. During the research, the authors used general scientific methods such as synthesis, system and comparative analyses. The authors of the article identified the key drivers of the ESG concept development which will contribute to the growth of not only a single company, but also of the country’s economy as a whole. Based on the results of the study the authors have developed recommendations for the implementation of the ESG strategy in the current geopolitical circumstances.